Temporal and Spatial Evolution of Precipitation under the Summer Sprite Parent Mesoscale Convective Systems in Japan - Tomoyuki Suzuki; Masashi Kamogawa; Hironobu Fujiwara; Syugo Hayashi (Atmosphere, 2022)
Transient luminous events (TLEs) are electrical discharges in the upper atmosphere caused by vigorous thunderstorms. Six sprites, which are part of TLEs, were observed on 22 July 2013 from Mt. Fuji (3776 m above sea level), Japan. All the six sprites were associated with intense positive cloud-to-ground strikes (+CGs), whose causative positive charges can reside in the stratiform region. Consequently, we assumed that the main sprites causative charges could generate an in situ charging mechanism, accompanied by precipitation growth in the extensive stratiform region. Thus, we supposed that there can be a relationship between the time sequence of surface precipitation intensity and the sprite emissions. In this study, we conclude that time sequences and horizontal evolution of Mesoscale Convective Systems (MCSs) precipitation are associated with sprites. As the result, prior to sprites 1–5, the areal amount of strong precipitation (≥8 mm/h) increased considerably, and only a small increase occurred during sprite 6. Analyzing the time sequence of the percentage of strong and weak precipitation with respect to the total precipitation, it was found that sprites 1–6 occurred within 20 min after the local peaks with respect to strong precipitation compared to total precipitation. In particular, sprites 2–5 occurred very close to local peaks. The rise time to the first peak of the strong precipitation rate associated with the first sprite was 80 min, while the rise time to the last peak associated with sprite 6 was 30 min. The temporal differences until the peaks suggest that the charging speeds, or mechanisms, related to precipitation differ between sprites 1–5 and sprite 6 in parent MCSs.